The Role Of Modern Training Technologies In The Success Of Sports Professionalism - Mekhazni , Mohammed; Ghadbane, Ahmed Hamza (sports creativity, 2025)
In this study the role and the importance of the use of modern technologies in the success of the training were addressed , and as a result, professionalism was achieved through content analysis’ approach, in which the content of three scientific studies was analyzed. The first compared the use of cameras from various angles to assess sports performance and GPS tracking systems, the second looked at video analysis programs and their impact on sports performance analysis, and the third looked at the use of technology in analyzing fitness performance factors. Through the analysis of these studies we can conclude that the technological methods of training are critical in evaluating all elements of sports performance, including the elements of fitness and their tests, as well as for the technical and tactical aspect, through an analysis of all the situations of the individual and collective aspects in their parts by modern techniques represented in video sports performance analysis programs. Through this analysis we can identify strengths of both; the individual and collective aspects; by means of modern techniques represented in video sports performance analysis programs, in addition